Social Isolation Blunted the Response of Mesocortical Dopaminergic Neurons to Chronic Ethanol Voluntary Intake - Lallai, Valeria; Manca, Letizia; Dazzi, Laura (Frontiers in Cellular Neuroscience, 2016)
Previous studies have shown that stress can increase the response of mesolimbic dopaminergic neurons to acute administration of drugs of abuse included ethanol. In this study we investigated the possible involvement of the mesocortical dopaminergic pathway in the development of ethanol abuse under stress conditions. To this aim we trained both socially isolated (SI) and group housed (GH) rats to self administer ethanol which was made available only two hours a day (from 11:00 to 13:00 hours). Rats have been trained for 3 weeks starting at postnatal day 35. After training, rats were surgically implanted with microdialysis probes under deep anesthesia, and 24 h later extracellular dopamine concentrations were monitored in mPFC for the two hours preceding ethanol administration (anticipatory phase), during ethanol exposure (consummatory phase) and for two hours after ethanol removal. Results show that, in GH animals, dopamine extracellular concentration in the mPFC increased as early as 80 min before ethanol presentation (+50% over basal values) and remained elevated for 80 min during ethanol exposure. In SI rats, on the contrary, dopamine extracellular concentration did not show any significant change at any time point. Ethanol consumption was significantly higher in SI than in GH rats. Moreover, mesocortical dopaminergic neurons in SI animals also showed a decreased sensitivity to an acute administration of ethanol with respect to GH rats. Our results show that prolonged exposure to stress, as in social isolation, is able to induce significant changes in the response of mesocortical dopaminergic neurons to ethanol exposure and suggest that these changes might play an important role in the compulsivity observed in ethanol addiction.